PERAN KONSELING INDIVIDU PENDEKATAN SOLUTION FOCUSED BRIEF COUNSELING (SFBC) UNTUK MENGATASI SELFISH PADA SISWA SMA NEGERI 1 COLOMADU TAHUN PELAJARAN 2025/2026 - Revalina Elisativani Krisania Lisdiono; Hera Heru Sri Suryanti; Ahmad Jawandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Revalina Elisativani K.L. THE ROLE OF INDIVIDUAL COUNSELING USING THE SOLUTION FOCUSED BRIEF COUNSELING (SFBC) APPROACH TO OVERCOME SELFISHNESS AMONG STUDENTS AT SMA N COLOMADU IN THE 2025/2026 ACADEMIC YEAR : The purpose of this study was to determine whether individual counseling can overcome selfish attitudes among students at SMA N COLOMADU using the Solution Focused Brief Counseling (SFBC) approach in the 2025/2026 academic year. This research was conducted at SMA N Colomadu, Colomadu District. The subjects of this study were the seventh-grade students, with the object being 1 selfish student and 1 peer of the selfish student. This was a descriptive qualitative research study conducted in 4 stages, where each stage included planning, implementation, results, and conclusion. The data analysis technique used was Miles & Huberman's model, which included the stages of data collection, data reduction, data presentation, and drawing conclusions. The data collection techniques used were interviews, observation, and documentation. According to the research results, the scaling question technique can help students increase their awareness of the importance of empathy, cooperation, and social concern within the school environment. Based on the results of the study on the role of individual counseling using the scaling question technique to reduce selfishness among seventh-grade students at SMA N Colomadu in the 2025/2026 academic year, it is concluded that individual counseling services with the scaling question technique can help students reduce their selfishness.